2000
DOI: 10.1097/00006123-200002000-00035
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Animal Models of Cerebral Vasospasm: A Review

Abstract: The model of SAH and vasospasm used most frequently is the canine "two-hemorrhage" model, in which two injections of blood into the dog's basal cistern performed 48 hours apart result in greater arterial vasoconstriction than that effected by a single injection of blood. On the basis of its ability to accurately predict what occurs in human SAH, the best model of vasospasm seems to be the primate model in which a blood clot is surgically placed around the large cerebral vessels at the base of the monkey's brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 122 publications
6
102
0
Order By: Relevance
“…generally been regarded as a poor model for study of delayed cerebral vasospasm (Macdonald and Weir, 2001;Meguro et al, 2001;Megyesi et al, 2000). However, based on the observation that the severity of cerebral vasospasm appears exponentially related to subarachnoid blood volume (Findlay et al, 1989;Kistler et al, 1983), several studies using a double hemorrhage model with cisterna magna injection have been performed in rats in recent years and could demonstrate angiographic and morphological changes of cerebral arteries similar to delayed vasospasm (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…generally been regarded as a poor model for study of delayed cerebral vasospasm (Macdonald and Weir, 2001;Meguro et al, 2001;Megyesi et al, 2000). However, based on the observation that the severity of cerebral vasospasm appears exponentially related to subarachnoid blood volume (Findlay et al, 1989;Kistler et al, 1983), several studies using a double hemorrhage model with cisterna magna injection have been performed in rats in recent years and could demonstrate angiographic and morphological changes of cerebral arteries similar to delayed vasospasm (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Megyesi et al (2000) concluded in a comprehensive review of more than 50 different experimental models of vasospasm that primates are best suited to simulate human delayed vasospasm. However, cost and animal rights issues considerably restrict the widespread use of these animal models.…”
Section: Introductionmentioning
confidence: 99%
“…2 Alterations of diameters of pial arterioles (lm, mean ± SD) after cisternal injection in the two groups. *P \ 0.05 vs. baseline or non-SAH method for producing SAH in rats is based on the introduction of fresh autologous arterial blood into cisterns, in which the delayed cerebral ischemia is not well simulated (Megyesi et al 2004;Sun et al 2003). In this experiment, cisternal injection of the frozen and thawed blood was used to induce SAH.…”
Section: Discussionmentioning
confidence: 99%
“…used to conduct studies about vasospasms after SAH, rat models of SAH are quite widespread. This is due to the ease in handling, housing and cost (Megyesi et al, 2000). Since the studies by Barry et al in 1979, multiple invasive models have been generated with large differences between them, without achieving the optimal model (Barry et al, 1979).…”
Section: Introductionmentioning
confidence: 99%